Asia falling? : - Henderson, Callum (McGraw-Hill, 1998)
1. The objective - growth at any price, 2. The hype - emerging market fever, 3. The warning - dollar-yen rebounds, 4. The precedent - Mexico, 5. The catalyst - Thailand...